Comparison of different nisin quantification methods and optimization of nisin production by Lactococcus lactis - Ersoy, Z. Girgin; Demir, G.; Cesur, M. F.; Gedik, S. Tunca (Wiley-Blackwell, 2016)
[No abstract available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY